PERAN SEKOLAH DALAM MENDIDIK GENERASI TOLERAN DI SEKOLAH DASAR - Willyam, Putri Cantika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the role of the school in educating a tolerant generation at SD Negeri 1 Singkawang. The research problem is the continuous intolerant behavior among students, such as mocking and forming groups based on ethnicity. The research uses a descriptive qualitative approach with a case study design. The research subjects consist of fifth-grade students, teachers, the principal, and parents. Data collection techniques include semi-structured interviews, participatory observation, and documentation. Data validity through triangulation of techniques and sources. Data analysis through data collection, reduction, presentation, and conclusion drawing. The research results show that the role of schools in educating a tolerant generation is carried out through school policies, habituation, modeling, conditioning, and integration in learning. The poem "Children Learn from Their Environment" serves as an important reflection that children learn from their surroundings. The conclusion of this research emphasizes that schools play a strategic role in instilling the value of tolerance through a holistic and contextual approach